2016
DOI: 10.1002/jhet.2665
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot Synthesis of Bis[1‐N,7‐N‐diethoxyphthalimido‐4,4′‐{3,5‐dimethyl‐4‐(4‐N,N‐dimethyl Aminophenyl)‐4,7‐dihydro‐1H‐dipyrazolo[3,4‐b;4′,3′‐e]Pyridin‐8‐yl}‐phenyl] Compounds and Their Antiviral Evaluation Against Cytomegalovirus (CMV) and Varicella‐zoster Virus (VZV) in Human Embryonic Lung (HEL) Cells

Abstract: A one‐pot three components synthesis of substituted bis[1‐N,7‐N‐diethoxyphthalimido‐4,4′‐{3,5‐dimethyl‐4‐(4‐N,N‐dimethylaminophenyl)‐4,7‐dihydro‐1H‐dipyrazolo[3,4‐b;4′,3′‐e] pyridin‐8‐yl}‐phenyl] in moderate to high yields has been achieved by a two‐step reaction. All the synthesized compounds evaluate against cytomegalovirus and varicella‐zoster virus in human embryonic lung cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Hussain et al (2017) have synthesized 4,4‐bis[{3,5‐dimethyl‐4‐(4‐substitutedphenyl)‐4,7‐dihydro‐ 1H ‐dipyrazolo[3,4‐b;4′,3′‐e]pyridin‐8‐yl}‐phenyl] compounds 183a‐e by one‐pot three‐component reaction of 5‐methyl‐2,4‐dihydro‐ 3H ‐pyrazole‐3‐one 179 , with substituted aldehydes 180 and p ‐phenylenediamine 181 using ethanol as a solvent (Scheme 29). Compounds 183a‐e were evaluated for their antiviral activity against cytomegalovirus (CMV) and varicellar‐zoster virus in HEL cells and results indicated that compound 183c was found to be active against AD‐169 in 9.71 μg/ml and a Davis strain of CMV is 7.06 μg/ml with its cytotoxicity in HEL cells >50 μg/ml.…”
Section: Enteroviruses and Herpesvirusesmentioning
confidence: 99%
“…Hussain et al (2017) have synthesized 4,4‐bis[{3,5‐dimethyl‐4‐(4‐substitutedphenyl)‐4,7‐dihydro‐ 1H ‐dipyrazolo[3,4‐b;4′,3′‐e]pyridin‐8‐yl}‐phenyl] compounds 183a‐e by one‐pot three‐component reaction of 5‐methyl‐2,4‐dihydro‐ 3H ‐pyrazole‐3‐one 179 , with substituted aldehydes 180 and p ‐phenylenediamine 181 using ethanol as a solvent (Scheme 29). Compounds 183a‐e were evaluated for their antiviral activity against cytomegalovirus (CMV) and varicellar‐zoster virus in HEL cells and results indicated that compound 183c was found to be active against AD‐169 in 9.71 μg/ml and a Davis strain of CMV is 7.06 μg/ml with its cytotoxicity in HEL cells >50 μg/ml.…”
Section: Enteroviruses and Herpesvirusesmentioning
confidence: 99%